Structure evolution with Sr content of the perovskite‐like materials La2−xSrxCoTiO6 (0 ≤x≤ 0.5). (1st April 2014) - Gómez‐Pérez, Alejandro; Pérez‐Flores, Juan Carlos; Ritter, Clemens; Boulahya, Khalid; Castro, German R.; García‐Alvarado, Flaviano; Amador, Ulises
<x xml:space="preserve">Abstract</x> The oxide series La2−xSrxCoTiO6 (0 ≤x≤ 1.0) belong to the perovskite family with general formula ABO3. The evolution of the room‐temperature structure as a function of the Sr content was studied using complementary techniques by applying the symmetry‐adapted modes formalism (AMPLIMODES). In the compositional range presented in this article (0 ≤x≤ 0.5), the compounds adopt distorted perovskite structures of monoclinic (space group P21/n) or orthorhombic (space group Pnma) symmetry, both with octahedral tilting scheme (a−a−c+) (out of phase along two perovskite main directions and in phase along the third direction). The main difference between these structures is the existence of rock‐salt order of B ions in the monoclinic symmetry, which is lost for x≥ 0.30. As the Sr content increases, a better matching of the A—O and B—O distances occurs. This is produced by an elongation of the A—O distance as La3+ is replaced by the larger ion Sr2+, and the shortening of the B—O distance due to the oxidation of Co2+ to Co3+ induced by the aliovalent substitution. As a result, the cuboctahedral A‐site cavity becomes less and less distorted; the A ion tends to occupy its ideal positions, increasing its coordination and giving rise to a more symmetrical structure. In the whole compositional range, the symmetry‐adapted atomic displacements (modes) responsible for the out‐of‐phase tilting of the BO6 octahedra remain active but those associated with the in‐phase tilting become negligible, anticipating for x≥ 0.6 a transition to a new structure with tilting scheme either (a0a0c−) (space group I4/mcm) or (a−a−a0) (space group Imma) or (a−a−a−) (space group R<inline-graphic xlink:href="ark:/27927/pgg55053hqn" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />c).